Breeding of the new peach variety Jiushuang - WANG Licheng; XIAO Xiao; WU Junkai; LIU Junming; LI Qingquan; LIU Jianzhen; SONG Liqin; ZHANG Libin (Guoshu xuebao)
Mancheng and Shunping counties, located in the central region of Hebei Province, are major peach-producing areas within the province. These regions encompass a substantial cultivation area of approximately 13 000 hectare. The main cultivated varieties in this region include Okubo, Yanhong, Honggangshan, Dajinghong, etc. The fruit harvesting season extends from early July to late August. Notably, the peak maturity of these peach varieties aligns with the rainy season, which markedly influences fruit quality. Consequently, the peaches exhibit a flat flavor and reduced resistance to storage and transportation. Currently, this region lacks late-maturing and high-quality peach varieties. Considering the existing gaps in the peach varieties, Hebei Normal University of Science and Technology has engaged in a collaborative breeding initiative with the Mancheng District Nursery in Baoding City, aiming to develop a peach variety characterized by late maturity and exceptional quality. Ultimately, the novel variety Jiushuang was successfully identified and developed from the natural progeny of Okubo. This variety is distinguished as a high-quality honey peach. The cultivar Jiushuang, originally identified as 28-19, was subjected to a rigorous and refined breeding regimen. In 2001, the breeding team at Hebei Normal University of Science and Technology harvested natural hybrid seeds from the Okubo peach orchard in the Changli region, which were subsequently subjected to in situ sand storage. In the spring of 2002, the seeds were sown within the greenhouse facilities at the Tangshan breeding station. Following extensive monitoring and assessment, the superior individual designated as 28-19 was identified as the primary candidate for cultivation, prompting the immediate initiation of seedling propagation efforts. By 2007, extensive multi-site trials in locations such as Qinhuangdao, Baoding, Tangshan, and Beijing, alongside the control variety, were conducted to assess the adaptability and stress resistance of 28-19, as well as to monitor the consistency and stability of its desirable traits. The trial outcomes indicated that the fruit of the 28-19 line matures approximately 25 days later than the control variety Okubo peach. Notably, the fruit from 28-19 is larger, exhibits vibrant coloration, a round shape, and superior quality, while also demonstrating good adaptability, high yield potential, and resistance to storage and transportation, with stable excellent traits. In 2022, DNA molecular analysis was performed on the superior line, confirming its status as a novel genotype. In September 2022, the Hebei Provincial Forest Variety Approval Committee convened a panel of experts for an on-site evaluation, which concluded that the superior line excelled in fruit traits, botanical features, and biological properties, displaying consistent performance across generations. In comparison to the control variety, 28-19 trees displayed distinct characteristics in terms of fruit maturity and morphological features, suggesting promising market potential. In April 2023, the Hebei Provincial Forest Variety Approval Committee officially designated this exceptional line as Jiushuang. The fruits of Jiushuang cultivar are spherical in morphology, featuring a flat and even apex along with a fruit suture of moderate depth. The fruits exhibit a basal color of milky white, and the surface is red- colored, with a coloration coverage of 60%. The average single fruit weight is 300 g, featuring white flesh with a concentration of red pigments near the stone. The fruit possesses a firm and soluble texture, accompanied by a cling stone. The soluble solids content is 13.5%, manifesting an optimally palatable sweet- tart flavor profile. The fruit development period spans 140 days, exhibiting the capability of self-fertilization. In the Mancheng District of Baoding City, the Jiushuang fruits ripen between late August and early September. In April 2023, this cultivar was officially endorsed by the Hebei Provincial Forest Tree Variety Appraisal Committee, and it was assigned the premium variety designation with the code: Ji S-SV-AP-009-2023.